Synthesis of Ethylphosphonate Curcumin Mimics: Substituents Allow Switching Between Cytotoxic and Cytoprotective Activities - Valeria Romanucci; Rita Pagano; Solveigh C. Koeberle; Andreas Koeberle; Minh Bui Hoang; Sonia Di Gaetano; Domenica Capasso; Michele Francesco Maria Sciacca; Valeria Lanza; Carmelo Tempra; Fabio Lolicato; Armando Zarrelli; et al. (Antioxidants)
Curcumin is recognized for its diverse biological activities, including the ability to induce apoptosis and ferroptosis. Therefore, it represents a promising candidate for the development of new compounds with neuroprotective and anticancer properties. In order to synthesize mimics with improved pharmacokinetic properties (better solubility and stability than curcumin) here, we present the design and synthesis of novel curcumin analogues named Ethylphosphonate-based curcumin mimics (EPs), which preserve the pharmacophoric features of curcumin. New EP mimics were synthesized by tyrosol- and melatonin-based building blocks using an orthogonal protection approach of the different precursors’ OH functions with good yields and in a few steps. Comparative screenings of the cytotoxic and cytoprotective properties (curcumin was used as a reference compound) were carried out on all new mimics in different cell lines (HeLa, A375, WM266, MDA-MB-231, LX2, and HDF). Assays with inhibitors of ferroptosis (Ferrostatin-1, Fer-1) and apoptosis (Quinoline-Val-Asp-difluorophenoxymethyl ketone, Q-VD), in combination with curcumin, suggested the specific cell death pathway (apoptotic or ferroptotic) of EPs, depending on the aromatic moieties contained in them. Interestingly, EP4 exhibited substantial cytotoxic effects against various human cancer cell lines (HeLa, A375, WM266) while sparing normal cells (HDFs). EP4 displayed a five-times-higher toxicity in triple-negative MDA-MB-231 and LX2 stellate cells than curcumin. The cytotoxicity exerted by EP4 involves only an apoptotic mechanism, contrary to curcumin, which exerts both apoptotic and ferroptotic effects. Additionally, EP4 was also found to be a very potent inhibitor of the ubiquitin-activating enzyme E1, reinforcing the anticancer potential of this compound. Furthermore, EP2 possesses high antioxidant properties, efficiently protects against cell death by ferroptosis, and inhibits the amyloid aggregation involved in AD.